Symbolic Systems and Cultural Continuity in Northwest Australia: A Consideration of Aboriginal Cave Art - Blundell, Valda (Culture, 1982)
Archaeological research in Australia suggests that Aboriginal foragers have successfully occupied the continent for many thousands of years. Furthermore, it appears that the trans-generational continuity of their cultural systems has been achieved in the face of a great deal of flux in the daily lives of individuals. This paper argues that Aboriginal cave art constitutes a set of symbols which have facilitated cultural continuity in the face of empirical variability.